An evaluation of the book and periodical collections of the Febias College of Bible Library - Oamil, Florida L. (1983)
This study is an attempt to analyze and evaluate the existing library holdings of the FEBIAS College of Bible. The purpose of the study is to evaluate the sufficiency of the book and periodical collections in relation to the curricular requirements of the college and to analyze its characteristics as to subject coverage and imprint dates. It has also explored the problem of whether the periodical collection is being utilized fully or not.